Polysomnographic measures of sleep in cocaine dependence and alcohol dependence: Implications for age‐related loss of slow wave, stage 3 sleep. (24th February 2016) - Irwin, Michael R.; Bjurstrom, Martin F.; Olmstead, Richard
Abstract: Background and aims: Sleep disturbance is a prominent complaint in cocaine and alcohol dependence. This controlled study evaluated differences of polysomnographic (PSG) sleep in cocaine‐ and alcohol‐dependent subjects, and examined whether substance dependence interacts with age to alter slow wave sleep and rapid eye movement (REM) sleep. Design: Cross‐sectional comparison. Setting: Los Angeles and San Diego, CA, USA. Participants: Abstinent cocaine‐dependent subjects ( n  = 32), abstinent alcohol‐dependent subjects ( n  = 73) and controls ( n  = 108); mean age 40.3 years recruited 2005–12. Measurements: PSG measures of sleep continuity and sleep architecture primary outcomes of Stage 3 sleep and REM sleep. Covariates included age, ethnicity, education, smoking, body mass index and depressive symptoms. Findings: Compared with controls, both groups of substance dependent subjects showed loss of Stage 3 sleep ( P  < 0.001). A substance dependence × age interaction was found in which both cocaine‐ and alcohol‐dependent groups showed loss of Stage 3 sleep at an earlier age than controls ( P  < 0.05 for all), and cocaine‐dependent subjects showed loss of Stage 3 sleep at an earlier age than alcoholics ( P  < 0.05). Compared with controls, REM sleep was increased in both substance‐dependent groups ( P  < 0.001), and cocaine and alcohol dependence were associated with earlier age‐related increase in REM sleep ( P  < 0.05 for all). Conclusions: Cocaine and alcohol dependence appear to be associated with marked disturbances of sleep architecture, including increased rapid eye movement sleep and accelerated age‐related loss of slow wave, Stage 3 sleep.